Freeze/thaw stability study of hotdog with carrageenan - Legaspi, Hannah Louisa Ugali
Hotdog samples containing 0%, .02%, 0.3%, 0.4%, and 0.5% Gelcarin® carrageenan were investigated. The samples were subjected to three freeze/thaw cycles. Physico-chemical analysis such as pH and % thaw drip were done on the samples, as well as consumer acceptability tests which were performed prior to the first freeze/thaw cycle and after each freeze/thaw cycle that followed. Results were analyzed using two-way ANOVA for the physico-chemical analysis and one-way ANOVA for the analysis of the results of consumer tests. Results showed that as the amount of carrageenan added to the samples increased, % thaw dip decreased. Based on the mean scores, consumer tests showed that samples containing 0.5% carrageenan were highly acceptable in terms of its textural characteristics while samples which contained no carrageenan were the least acceptable for this particular and specific attribute. All samples showed no significant change in pH throughout the freeze/thaw cycles.